Kernel Nutrient Composition and Antioxidant Ability of Corylus spp. in China - Jiang, Jiangzhao; Liang, Lisong; Ma, Qinghua; Zhao, Tiantian (Frontiers in Plant Science, 2021)
Hazelnut (Corylus) is an important woody oil tree species in economic forests. China, as one of the original countries of native Corylus species, had 8 species and 2 varieties. However, little information is available on the nutritional quality of these species. In this study, four main wild Corylus species originating (C. heterophylla Fisch., C. mandshurica Maxim., C. kweichowensis Hu. and C. yunnanensis Franch.) and one main cultivar of Ping’ou hybrid hazelnut (Corylus heterophylla Fisch. × C. avellana L.) from China were used to analyze the basic nutritional composition (content of oil, fatty acid, protein, saccharide, aminao acid, vitamin C, tocopherol, total phenols,and total flavonoids) and antioxidant ability. The results showed that oil content ranged from 52.97 g/100 g DW to 60.88 g/100 g DW and highly unsaturated fatty acid content was over 91 percent. Oleic was the most dominant UFA in these kernels, and the relative content was ranging from 71.32 % to 85.19 %. Compared with other four species, C. heterophylla Fisch. was the lowest oil content with lower oleic acid content and higher linoleic acid content, obviously. The total protein content ranged from 13.15 g/100 g DW to 18.35 g/100 g DW, and all amino acids were detected as hydrate amino acids, but Tryptophan, an essential amino acid, was not detected as free amino acid in these kernels. C. heterophylla Fisch. was with the highest content of protein and amino acid. Saccharose was the most essential and abundant disaccharide in the hazelnut kernels. C. mandshurica Maxim. was the hightest saccharide content among these hazelnut kernels. α-tocopherol was the main type of tocopherol found in the hazelnut kernels. Wild hazelnut kernels generally had higher bioactivity substance content (vitamin C, total tocopherol, total phenol and total flavonoid) and antioxidant capacity. Compared to the four wild species, the Ping’ou hybrid had higher content of oil, oleic acid, α-tocopherol and sugar. Overall, there were great differences in the nutritional composition of these species. Wild species are a good source of breeding materials because of their own characteristics in nutrition composition, and hybrid hazelnut with good quality has the value of commercial promotion.